COVID-19: BEHAVIOR OF PUBLIC FINANCES TOOLS IN DEMOCRATIC REPUBLIC OF CONGO. ECONOMIC SITUATION AND PERSPECTIVES - LUBONGO MBILU, Yannick (Theoretical and Practical Research in Economic Fields, 2021)
Observation of economic life over a long period portrays a succession of phases in which the economic activity is somehow important or decreasing. This succession can either be caused by an endogenous or exogenous sector shock. This health shock, due to Covid-19, has compromised the macroeconomic stability as well as the economic growth in DRC, even across the world, according to their impact. Additionally, it is the cause of a reduction of the economic activity and has resulted in a huge instability of the global supply and demand. Congolese economy has not experienced satisfactory outcomes, thereby, a conjectural analysis of public finance macroeconomic aggregates enabled to comprehend this situation. Regarding the hypothesis’s verification, there are variables of income and outlay of independent samples, variables whose variances and means are equal both in the presence or the absence of Covid-19. In the same way, other variables and means are considerably different one another.